1989
DOI: 10.1128/mcb.9.12.5702-5712.1989
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Transcriptional Control by Heme of Genes Encoding 3-Hydroxy-3-Methylglutaryl Coenzyme A Reductase in Saccharomyces cerevisiae

Abstract: Responses of the yeast genes encoding 3-hydroxy-3-methylglutaryl coenzyme A reductase, HMG1 and HMG2, to in vivo changes in heme concentrations were investigated. Expression of the genes was determined by direct measurement of the mRNA transcribed from each gene, by direct assay of the enzyme activity encoded by each gene, and by measurement of the expression of lacZ fusions to the control regions of each gene. These studies indicated that expression of HMG1 was stimulated by heme, whereas expression of HMG2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Both miconazole and sulconazole induced ARE1 expression and repressed ARE2 expression (Table 3). This opposing effect of a treatment on the two isozymes of an enzymatic activity has been seen before in the yeast sterol pathway (2,4). In contrast, fluconazole treatment induced both ARE1 and ARE2 (Table 3).…”
Section: Mechanism Of Lanosterol Demethylase Inhibitorssupporting
confidence: 66%
See 1 more Smart Citation
“…Both miconazole and sulconazole induced ARE1 expression and repressed ARE2 expression (Table 3). This opposing effect of a treatment on the two isozymes of an enzymatic activity has been seen before in the yeast sterol pathway (2,4). In contrast, fluconazole treatment induced both ARE1 and ARE2 (Table 3).…”
Section: Mechanism Of Lanosterol Demethylase Inhibitorssupporting
confidence: 66%
“…This feedback regulation is keyed to multiple intermediates and appears to act at numerous steps of the pathway, involving changes in transcription, translation, and protein stability. Additionally, the availability of molecular oxygen, required for sterol and heme biosynthesis, also regulates the expression of genes at key steps of the pathway (4,5). The emerging picture is that the isoprenoid pathway has numerous points of regulation that act to control overall flux through the pathway as well as the relative flux through various branches of the pathway.…”
mentioning
confidence: 99%
“…23 S. cereVisiae encodes two isozymes of this protein, Hmg1p and Hmg2p. Although the yeast isozyme Hmg1p is regulated by transcription, 24 translation, 25 and ubiquitin-mediated proteolysis, 26 removing the noncatalytic N-terminal transmembrane-spanning domain (1656 nucleotides) from Hmg1p generates an active, cytosolic truncated protein. High-level expression of the truncated Hmg1p significantly increases accumulation of the sterol precursor squalene.…”
mentioning
confidence: 99%
“…Thorsness et a/. 16 have shown that, in the presence of heme, expression of HMGl is stimulated whereas HMG2 is repressed. This effect is not uncommon for pairs of genes which encode isozymes.…”
Section: Mevalonic Acidmentioning
confidence: 99%
“…g OGlc have examined the biosynthesis of dihydrocornin (16) and cornin (17) in whole plants of Verbena oficinalis. In a comprehensive study, I3Clabelled 8-hydroxygeraniol (12), iridial (13), iridotrial (14), deoxyloganin (13, and other putative precursors were synthesized and fed.…”
Section: Monoterpenoidsmentioning
confidence: 99%